Identification of Chilli leaf curl virus associated with tomato leaf curl betasatellite infecting Mentha in Oman. Issue 2 (3rd April 2019) - Shahid, Muhammad Shafiq; Raza, Amir; Al-Sadi, Abdullah M.; Briddon, Rob W.
Abstract: Mint ( Mentha sp.; family: Lamiaceae ) plants showing yellowing and stunting symptoms from Salalah, Dhofar region, Oman were shown to be infected by a monopartite begomovirus (family: Geminiviridae ). Cloning and sequencing of restriction endonuclease digested rolling-circle amplified viral DNA identified a begomovirus associated with the symptomatic mint plants. Further analysis of complete sequences showed the virus to be a variant of the 'Oman' strain of Chili leaf curl virus (ChLCV-OM), a virus prevalent in a number of crops across Oman. However, the ChLCV-OM identified in mint has a recombination pattern distinct from all other ChLCV isolates. Additionally, PCR amplification and sequencing showed the mint plants to also harbour the betasatellite, Tomato leaf curl betasatellite (ToLCB). This is the first identification of ChLCV in association with ToLCB infecting mint. The distinct recombination pattern of ChLCV-OM from mint suggests that the host is epidemiologically important in the spread of ChLCV-OM to other crops in Oman.